中継装置、送信装置、通信システムおよび通信方法 (2012)
ＲＮ（１００）は、ＵＥへ無線信号を送信してから所定期間後に無線信号に対する送達確認情報を受信するｅＮＢとＵＥとを含む通信システムの中継装置である。ＤＬ受信機（１１０）は、ｅＮＢから送信された無線信号を受信して復号する。中継判断部（１３０）は、ＤＬ受信機（１１０）によって復号された無線信号がＲＮ（１００）の中継対象か否かを判断する。中継情報生成部（１４０）およびＵＬ＿ＰＨＹ処理部（１５０）は、中継判断部（１３０）によって中継対象であると判断された場合に、無線信号を再生中継することを示す中継情報をｅＮＢへ通知する。ＤＬ送信機（１７０）は、中継判断部（１３０）によって中継対象であると判断された無線信号をＵＥへ送信する。 An RN (100) is a relay apparatus of a communication system that includes a UE and an eNB that after a given period that starts after the transmission of a wireless signal to the UE, receives delivery confirmation information concerning the transmitted wireless signal. A DL receiver (110) receives and decodes the wireless signal transmitted by the eNB. A relay determiner (130) determines whether the wireless signal decoded by the DL receiver (110) is subject to relay by the RN (100). If the relay determiner (130) determines that the wireless signal is subject to relay, a relay information generator (140) and a UL_PHY processor (150) notify the eNB of relay information indicating that the wireless signal is to be regenerated and relayed. A DL transmitter (170) transmits to the UE, the wireless signal that has been determined to be subject to relay by the relay determiner (130).